INFORMATION SYSTEM REVENUE AND RECEIVABLES IN HOSPITALS BHAKTI WALUYO - Andrijanni Andrijanni; Drs.H.Soetirto Sadikin, MA (Jurnal Sistem Informasi, 1997)
Association as a booster for the writer to discuss this problem is to compare the writerhas gained knowledge during the lecture on STI & K Jakarta with reality in the field,especially in the areas of revenue and receivables as well to meet the requirements incompleting course strata-1.Aim of this study is to assist hospitals in obtaining revenues and accounts receivableeffectively and efficiently, and solve the problems and assist management in makingdecisions.The research methodology used is the study of comparative literature as acomplement to terhadapa problems encountered are analyzed as well as field researchand interviews with the viewer directly as a liaison group should study with the objectbeing studied.From the research the authors found several weaknesses in the current system, amongothers, there are weaknesses in the system of giving discounts to patients who are lessable, results delivery charges, and the difficulty of collecting data from existing parts.Because of the weakness is the author suggested to hold a revamping of the currentsystem, by designing a new system.